Gender stereotyping of northern Italian female adolescents' physical activity : a male perspective - Retis, Irene (2018)
This study aims to provide an overview of the conditions of Italian female adolescents in the sphere of sport and physical activity through the perceptions and understanding of their male peers. The intention of this study is to analyze the adolescent males’ viewpoint to unearth gender stereotypes and their implications on Italian female adolescents’ behavior on sports and physical activity in two different environments, namely the curricular and extracurricular environment. This study is implemented through qualitative research method. The data were collected through semi-structured interview techniques with 10 respondents. Respondents were 18/19-years-old adolescents living in the province of Vicenza, Veneto, Italy. The results of the research highlight the condition of Italian female adolescents in the sphere of sport and physical activity and the barriers that prevent and limit girls’ physical activity participation caused by gender stereotyping. Moreover, interviewees recognized a significant difference in the practice of sports and physical activity according to gender. It is recognized that Italian adolescent females face gender stereotypes both in the curricular and extracurricular environment through the perception of the existence of different sport according to gender, namely the feminine sports and through the lack of self-esteem and low self perception of female adolescents. Competitiveness and team sports were also recognized as an impediment to physical activity. Common societal norms were considered the main responsible for the limitation of physical activity for female adolescents. Based on the results, it is recommended for competent authorities to pay particular attention to the existing gender gap in the delivery of sports policies. In fact, the current degree of stereotyping in the Italian society urges in a recommendation for a closer attention to this issue, is order to prevent and to ease the practice of sport for youngest adolescent females. Moreover, research should be continued with a great care on this topic, to bring more attention on the subject, to understand the impact of stereotypes on sport behaviors, and to learn how to overcome them. Also, Italian school policies require particular attention in the delivery of the physical education classes, keeping in mind the different needs and preferences of their students.